Mobilisasi Dukungan dan Simpati Publik Terhadap Palestina pada Akun @Erlanishere di Twitter - Sinta Nur Azizah; Masnia Ningsih; Moch. Ichdah Asyarin Hayau Lailin (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
Twitter has become a social media that is widely used to communicate, communicate information, obtain information, and is often used as a place to discuss issues such as the Israeli-Palestinian conflict. The @erlanishere account is one of the humanitarian activists who regularly posts about the Palestinian situation. The stories presented not only provide information, but also arouse the emotions of the public and raise awareness and solidarity with the suffering of the Palestinian people. So this account is appointed as the Commander of the Netizen Julid Anti-Israeli Special Operations Unit. Only by using the tag, @erlanishere can coordinate netizens to voice the Israeli conflict in Gaza. In this way, the information can spread to netizens throughout Indonesia. The research into @erlanishere's account aims to understand the narrative of Israeli atrocities in Palestine and their impact on public perceptions. Using the critical discourse analysis method by Teun A.Van Dijk, the results of the research on this @erlanishere account were, able to mobilize public support and sympathy for Palestine, through the use of emotional language, visualizing violence, and presenting critical facts about Israeli actions.